Asthenosphere-induced melting of diverse source regions for East Carpathian post-collisional volcanism - Bracco Gartner, Antoine J. J.; Seghedi, Ioan; Nikogosian, Igor K.; Mason, Paul R. D. (Contributions to mineralogy and petrology, 2020)
The occurrence of post-subduction magmatism in continental collision zones is a ubiquitous feature of plate tectonics, but its relation with geodynamic processes remains enigmatic. The nature of mantle sources in these settings, and their interaction with subduction-related components, are difficult to constrain using bulk rocks when magmas are subject to mixing and assimilation within the crust. Here we examine post-collisional magma sources in space and time through the chemistry of olivine-hosted melt inclusions and early-formed minerals (spinel, olivine and clinopyroxene) in primitive volcanic rocks from the Neogene–Quaternary East Carpathian volcanic range in Călimani (calc-alkaline; 10.1–6.7 Ma), Southern Harghita (calc-alkaline to shoshonitic; 5.3–0.03 Ma) and the Perșani Mountains (alkali basaltic; 1.2–0.6 Ma). Călimani calc-alkaline parental magma compositions indicate a lithospheric mantle source metasomatised by ~ 2% sediment-derived melts, and are best reproduced by ~ 2–12% melting. Mafic K-alkaline melts in Southern Harghita originate from a melt- and fluid-metasomatised lithospheric mantle source containing amphibole (± phlogopite), by ~ 5% melting. Intraplate Na-alkaline basalts from Racoș (Perșani) reflect small-degree (1–2%) asthenosphere-derived parental melts which experienced minor interaction with metasomatic components in the lithosphere. An important feature of the East Carpathian post-collisional volcanism is that the lithospheric source regions are located in the lower plate (distal Europe-Moesia), rather than the overriding plate (Tisza-Dacia). The volcanism appears to have been caused by (1) asthenospheric uprise following slab sinking and possibly south-eastward propagating delamination and breakoff, which induced melting of the subduction-modified lithospheric mantle (Călimani to Southern Harghita); and (2) decompression melting as a consequence of minor asthenospheric upwelling (Perșani).